A Semantic Analysis of Minangkabaunese Verbs Connected to The Semantic Primes Touch: A Natural Semantic Metalanguage Study - Karina Safira Rannas; Rusdi Noor Rosa (Universitas Negeri Padang, 2020)
AbstractThis article analyzed words in Minangkabaunese that share the same semantic prime: TOUCH using Natural Semantic Metalanguage (NSM). This research was conducted using the descriptive qualitative approach. The data that were found in this research were the words connected that are connected to the semantic prime TOUCH in Minangkabau language. The sources of this data were the 11 informants from the 11 districts in Padang city, which is the capital city of the West Sumatera Province. The data were collected using interview guidelines, recording equipment, and writing equipment. An interactive model of data analysis is used to analyze the data. From the data that were collected and analyzed there are a total of 6 words that are connected to semantic prime TOUCH: maawai, manggaduah, maambiak, marabuik, marameh, and maresek. These words are similar but not exactly synonymous that they will create a misconception in diction.